1998
DOI: 10.1111/j.1699-0463.1998.tb00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 inhibits in vitro differentiation and selected functions of human blood‐derived monocytes

Abstract: We have studied the effect of herpes simplex virus type 1 (HSV1) infection on in vitro differentiation of blood‐derived human monocytes into macrophages using morphological, functional and biochemical parameters that alter during macrophage differentiation. Purified preparations of HSV modified the monocyte‐macrophage differentiation, in spite of the fact that the virus did not replicate in monocytes. Disappearance of expression of a monocyte‐specific surface antigen and the typical development of morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Previous studies showed that monocytes were resistant to HSV-1 infection, and only become susceptible to it upon differentiation towards macrophages (21)(22)(23). Another study showed that human peritoneal macrophages become partially permissive to viral infection upon treatment with thioglycollate, and are fully permissive after prior infection with Corynebacterium parvum (24).…”
Section: Hsv-1 Infection Induces Apoptosis In Human Monocytic Cellsmentioning
confidence: 99%
“…Previous studies showed that monocytes were resistant to HSV-1 infection, and only become susceptible to it upon differentiation towards macrophages (21)(22)(23). Another study showed that human peritoneal macrophages become partially permissive to viral infection upon treatment with thioglycollate, and are fully permissive after prior infection with Corynebacterium parvum (24).…”
Section: Hsv-1 Infection Induces Apoptosis In Human Monocytic Cellsmentioning
confidence: 99%
“…We recently demonstrated that tumor endothelium in murine ID8-VEGF ovarian tumors (and human ovarian cancer) derives in significant part from monocyte/dendritic cell precursors (Conejo-García et al, 2004). Mouse (and human) monocytes and immature dendritic cells are susceptible to HSV infection (Hayward et al, 1993;Weir and Elkins, 1993;Bruun et al, 1998;Kobelt et al, 2003;Pollara et al, 2003). The potent inflammatory response set off by the viral infection may massively recruit such cells into the tumor.…”
Section: Discussionmentioning
confidence: 99%